Pengembangan Buku Matematika Berbasis Cerita Dongeng Pada Materi Bilangan Untuk Meningkatkan Kemampuan Berhitung Siswa - Wulandari , Dinda Amalia (UIR PRESS, 2025)
Teachers only focus on using package books in teaching in the classroom. Learning is only a repository, that is, learning is very monotonous. As a result, students do not show great enthusiasm, students have difficulties and are unable to think logically, creatively and innovatively in developing their answers when working on math problems. This study aims to determine the feasibility, practicality and effectiveness of the pocket book. This research is a research and development or R&D with a 4-D to 3-D model. Then the results of V Aiken's calculation, student response data of 0.71 and teacher response data of 0.925 are classified as very practical to use during learning. Meanwhile, the calculation of the t-Paired test on the results of the pretest and posttest obtained a value of, t-calculating.=6.1807 and a value of ,t-table.=2.039 with an N-Gain value of 82.6%, so there was an increase in students' numeracy so that the book was categorized as very effective. The conclusion is that math books based on fairy tales can improve the numeracy skills of 2nd grade students of MIS Suhairiyah.